Hubungan Pengetahuan Dengan Sikap Ibu Hamil Terhadap Imunisasi Tetanus Toksoid - Sofiyati Sofiyati; Linawati Kuswanda (EDUPEDIA Publisher, 2023)
Objective: This study aims to determine the relationship between knowledge and attitude of pregnant women regarding Tetanus Toxoid (TT) immunization in the work area of Astapada Community Health Center, Tengah Tani Sub-District, Cirebon District. Methods: This research is a non-experimental descriptive study with cross-sectional retrospective data collection. This study involved 55 pregnant women who visited the Astapada Health Center for pregnancy checks as respondents. Results: Of the 55 pregnant women respondents under study, most of the respondents had a moderate level of knowledge on TT immunization or a many as 42 respondents (76.4%). Of the 42 respondents, 35 respondents (83.3%) had a positive attitude and 7 respondents (16.7%) had a negative attitude. The results of this study proved that there was a significant relationship between knowledge and attitude of pregnant women on Tetanus Toxoid Immunization in the Work Area of Astapada CHC, Tengah Tani Sub-District, Cirebon District with a p-value of 0.001 (p <0.05). Conclusion: There is a significant relationship between knowledge and attitude of pregnant women on Tetanus Toxoid Immunization in the Work Area of the Astapada CHC, Tengah Tani Sub-District, Cirebon District with a p-value of 0.001 (p <0.05).